Islamic workplace spirituality influence on organizational effectiveness of Indonesian States’ Islamic Higher Education Institutions - Mohd Ali, Hairuddin; Shohib, Muhammad Wildan; Ibrahim, Mohd Burhan (SAGE, 2022)
The study aimed to investigate the influence of Islamic workplace spirituality (IWPS) on organizational effectiveness (OE) of Indonesian States’ Islamic Higher Education Institutions (ISIHEIs) and to validate the psychometric properties of IWPS-OE instruments employed. A survey instrument using five-point Likert scale was administered to collect the data from 450 academic staff of six ISIHEIs across Java, Indonesia. Confirmatory factor analysis and complete structural equation modeling software were performed to test the factorial validity of each constructs under study and the hypothesized model. The results of study had established valid and reliable four-factor IWPS and three-factor OE sub-constructs. The tested and validated structural hypothesized model of the study exhibited substantial direct and significant influence of IWPS on OE of ISIHEIs. The findings of the study suggested that the articulation of IWPS could be practiced effectively in the context of ISIHEIs in enhancing the effectiveness of the higher education institutions. The study has successfully tested, formulated, and validated the hypothesized model of IWPS-OE of ISIHEIs and consequently enriching the related body of knowledge